2020
DOI: 10.1002/asia.202000814
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Activated C−C Bond Cleavage and Aerobic Oxidation of Benzyl Alcohols Employing BiMXO5 (M=Mg, Cd, Ni, Co, Pb, Ca and X=V, P)

Abstract: The synthesis, structure, optical and photocatalytic studies of a family of compounds with the general formula, BiMXO 5 ; M = Mg, Cd, Ni, Co, Pb, Ca and X = V, P is presented. The compounds were prepared by regular solid-state reaction of constituents in the temperature range of 720-810°C for 24 h. The compounds were characterized by powder X-ray diffraction (PXRD) methods. The Rietveld refinement of the PXRD patterns have been carried out to establish the structure. The optical absorption spectra along with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 116 publications
1
15
0
2
Order By: Relevance
“…算材料的电子结构, 具体的计算操作在 Wien2K [29] 软 件包中进行。采用 Perdew-Burke-Ernzerhof (PBE)版本 的广义梯度近似(Generalized Gradient Approximation, GGA) [30] 来描述交换相关函数, 赝势选择投影缀加 波(Projector Augmented Wave, PAW)法 [31][32] 。平面波 旋-轨道分裂峰, 说明两种样品 Bi 离子均为+3 价 [33][34][35] 。 图 4(b)为 Mn 的高分辨 XPS 谱图, 两种样品中 Mn 离子均出现了位于 640.8 和 653.1 eV 附近的双峰, 对 应于 Mn2p 3/2 和 Mn2p 1/2 的分裂峰, 结合能为 647 eV 左右的卫星峰为 Mn 2+ 离子的特征峰, 说明两种样品 中 Mn 离子均为+2 价 [36][37] 。 图 4(c)是 V 的高分辨 XPS 谱图, 图中 V2p 由两个能谱峰组成, 结合能分别位 于 516.7 和 524.4 eV 左右, 对应于 V2p 3/2 和 V2p 1/2 的分裂峰 [33][34][35] 。 如图 4(d)所示, 两种样品中 O1s 能谱 峰均位于 529.9 eV 左右, 对应于 BiMnVO 5 中的晶格 氧(O 2-) [33][34][35] 。 因此, 两种方法合成的 BiMnVO 5 粉体 中 Bi、Mn、V、O 的化合价分别为+3、+2、+5、-2。 采用 Kubelka-Munk 方程 [38] 可以将材料的反射 光谱转变为吸收数据, 如式 1 所示。 (2.45 eV) [2] 、 BiCdVO 5 (2.45 eV) [24] 、BiCu 2 VO 5 (2.1 eV) [25] 。…”
Section: 采用基于密度泛函理论(Dft)的第一性原理计unclassified
See 1 more Smart Citation
“…算材料的电子结构, 具体的计算操作在 Wien2K [29] 软 件包中进行。采用 Perdew-Burke-Ernzerhof (PBE)版本 的广义梯度近似(Generalized Gradient Approximation, GGA) [30] 来描述交换相关函数, 赝势选择投影缀加 波(Projector Augmented Wave, PAW)法 [31][32] 。平面波 旋-轨道分裂峰, 说明两种样品 Bi 离子均为+3 价 [33][34][35] 。 图 4(b)为 Mn 的高分辨 XPS 谱图, 两种样品中 Mn 离子均出现了位于 640.8 和 653.1 eV 附近的双峰, 对 应于 Mn2p 3/2 和 Mn2p 1/2 的分裂峰, 结合能为 647 eV 左右的卫星峰为 Mn 2+ 离子的特征峰, 说明两种样品 中 Mn 离子均为+2 价 [36][37] 。 图 4(c)是 V 的高分辨 XPS 谱图, 图中 V2p 由两个能谱峰组成, 结合能分别位 于 516.7 和 524.4 eV 左右, 对应于 V2p 3/2 和 V2p 1/2 的分裂峰 [33][34][35] 。 如图 4(d)所示, 两种样品中 O1s 能谱 峰均位于 529.9 eV 左右, 对应于 BiMnVO 5 中的晶格 氧(O 2-) [33][34][35] 。 因此, 两种方法合成的 BiMnVO 5 粉体 中 Bi、Mn、V、O 的化合价分别为+3、+2、+5、-2。 采用 Kubelka-Munk 方程 [38] 可以将材料的反射 光谱转变为吸收数据, 如式 1 所示。 (2.45 eV) [2] 、 BiCdVO 5 (2.45 eV) [24] 、BiCu 2 VO 5 (2.1 eV) [25] 。…”
Section: 采用基于密度泛函理论(Dft)的第一性原理计unclassified
“…光催化降解有机污染物在污水净化领域具有广 阔的应用前景 [1] 。钒酸铋(BiVO 4 )是一种典型的半导 体光催化剂, 其禁带宽度为 2.45 eV, 且具有化学性能 稳定和无毒等特点, 受到了广泛关注 [2][3][4] 。在 BiVO 4 的众多物相中, 具有单斜白钨矿结构的 BiVO 4 催化 性能最优, 这是由于单斜相中 Bi-O 多面体畸变程 度高, 有利于光生电子-空穴对的产生与分离 [5] 。然 而, BiVO 4 仅吸收部分可见光, 太阳能利用率低。因 此, 如何提升这类材料的光吸收效率是当前研究的 重点。 通过掺杂可以调控 BiVO 4 的禁带宽度, 提升光 吸收效率。Zhou 等 [6] 通过 Co 掺杂成功将其禁带宽 度降低至 2.39 eV, 光催化反应 5 h 后, MB 降解率提 升 20%。He 等 [7] 采用模板法制备了 Cu 掺杂 BiVO 4 纳米棒, 获得的最低禁带宽度为 2.02 eV。Regmi 等 [8][9] 采用水热法合成了 Fe 或 Ni 掺杂的 BiVO 4 , 获 得的最小禁带宽度约为 2.37 eV。此外, 研究人员还 尝试利用 Mo、W、In、Ln (Ln=Y、La、Sm、Gd)等元 素对 BiVO 4 进行掺杂, 但未能有效减小其禁带宽 度 [10][11][12][13][14][15][16][17] 。 然而, 掺杂对禁带宽度的调控范围有限, 且 杂质能级通常是光生电子-空穴对的复合中心。因此, 探索基于 BiVO 4 的新型窄带隙半导体具有重要的科 学意义和实用价值。 向 BiVO 4 体系中引入合适的结构基元, 形成具 有不同结构功能区的 Bi-M-V-O 多元化合物体系可 以有效调控其禁带宽度。 目前, 四元 Bi-M-V-O 体系 的化合物主要有 BiCdVO 5 、BiMnVO 5 、BiM 2 VO 6 (M=Zn、Cd)、BiCu 2 VO 6 、BiAe 2 VO 6 (Ae=Mg、Ca) 等 [18][19][20][21][22][23] 。 其中 Ae 元素的电正性较强, 会增大体系的 禁带宽度。过渡金属 Zn 和 Cd 中满占据的 nd 轨道 能量较低, ns 空轨道能量较高, 对费米能级附近的 能带结构贡献少, 难以调控其禁带宽度。Bhim 等 [24] 采用固相法制备了 BiCdVO 5 , 其禁带宽度(2.45 eV) 与 BiVO 4 接近, 且在光催化苯甲醇转化为苯甲醛的 反应中表现出较高的活性和选择性。部分占据的 Cu 2+ 3d 轨道和 Mn 2+ 3d 轨道可以有效抬升价带能量, 从而降低材料的禁带宽度。Liu 等 [25] 采用固相法制 备了 BiCu 2 VO 6 , 其禁带宽度为 2.1 eV, 且表现出优 于 BiVO 4 的光催化性能。然而, BiCu 2 VO 6 的禁带宽 度未在最佳光吸收的范围内((1.50.3) eV), 光吸收 效率仍较低。图 1 为引入 Mn 2+ 导致禁带宽度降低的 示意图。MnO 的价带顶为 Mn3d 和 O2p 轨道, 导带 底为 Mn3d 轨道, 禁带宽度为 3.8 eV [26][27] ; 而 BiVO 4 的价带顶为 Bi6s 和 O2p 轨道, 导带底为 V3p 轨道, 禁带宽度为 2.45 eV [28]…”
unclassified
“…In 2020, Natarajan and co-workers performed a comparative study in which they characterized various BiMXO 5 (M = Mg, Cd, Ni, Co, Pb, Ca and X = V, P) materials using powder X-ray diffraction and optical absorption methods. 74 BiCdVO 5 was potentially a promising catalyst due to its advantageous­ chemical stability and accessible band gap (2.45 eV). 75 For this reason, nano and bulk BiCdVO 5 were assessed in the aerobic, oxidative C=C bond cleavage reaction of styrene, which revealed the strong photocatalytic ability of the nanocatalyst in the model reaction (81%).…”
Section: C=c Bond Cleavagementioning
confidence: 99%
“…It is of great importance and challenging to choose proper catalytic system and investigate the oxidation of benzyl alcohols to aldehydes. [36][37][38][39][40][41][42] Very recently, we found that the nano-composite bimetal oxides-SBA-15 materials provided an easy access to the aerobic oxidation of benzyl alcohols in air. Thus, we report a new approach to the selective oxidation of benzyl alcohols to aldehydes that are of industrial and chemical importance.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, the development of new strategies aimed at improving synthetic efficiency is an important goal in current organic synthesis. It is of great importance and challenging to choose proper catalytic system and investigate the oxidation of benzyl alcohols to aldehydes [36–42] . Very recently, we found that the nano‐composite bimetal oxides‐SBA‐15 materials provided an easy access to the aerobic oxidation of benzyl alcohols in air.…”
Section: Introductionmentioning
confidence: 99%